Being a Francophone Parent with Children in Dutch-medium Education in Brussels: A Tale of Tensions and Competing Discourses - Van Mensel, Luk (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2016)
In the officially bilingual (French–Dutch) Brussels Capital Region (Belgium), education is largely organized in two parallel but separate systems: French-medium education and Dutch-medium education. Parents must choose to send their children to either a Dutch- or a French-medium school. The choice of one education system over another may generate identity-related issues, such as the idea—rooted in nationalism—that “being a French speaker” and “sending your children to Dutch-medium education” are identity options that are by definition conflicting. In this article, I present a case study of a Francophone couple who decided to enroll their children in a Dutch-medium school in Brussels. Even if this decision brought the parents closer to Dutch-speaking social networks, it also highlighted the tensions and contradictions between the various identity options available. The study shows how these parents, in trying to deal with these tensions, appeal to quite different and sometimes contradictory discourse on language and belonging.